Epidemiological and clinical features of talaromycosis (Penicilliosis) marneffei among human immunodeficiency virus-infected patients in Malaysia - Syaziah I; Azura SS; Tzar Mohd Nizam Khaithir (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
The AIDS epidemic in Southeast Asia has led to a marked rise in the incidence of talaromycosis (penicilliosis) marneffei. The aim of this cross-sectional study was to determine the clinico-epidemiological features and outcome predictors of talaromycosis in Malaysia. We identified Talaromycosis marneffei cases from cultures of sterile specimens from 191 human immunodeficiency virus (HIV)- infected patients. Talaromycosis increased from 20-25 (2010-2011) to 45-50 cases per year (2012-2014). Talaromycosis was the HIV-presenting illness in 117 (61.3%) patients. The incidence of talaromycosis as HIV-presenting illness showed an increasing trend from 10.7 (2010) to 26.4 (2014) cases per 1000 new HIV patients. The patients were between 19 and 74 of age (mean 37.2+9.4 years) and the male to female ratio was 7.7:1. Malay (73, 38.2%) and Chinese (70, 36.3%) were the most prevalent ethnic groups. Common clinical manifestations included loss of weight (85.9%), fever (84.8%) and cough (67%), while skin lesions were only present in 42.9% cases. Common concurrent infections were oral candidiasis (79.6%), tuberculosis (36.1%) and hepatitis C infection (20.9%). Most patients (93.7%) were anaemic with mean haemoglobin level of 9.9+2.3 g/dL, 39% had impaired liver function, and 18.8% were neutropaenic. Median CD4 cell count was 16 cells/L. Most patients (70.4%) received intravenous amphotericin B followed by itraconazole. At 8-month follow up, 148 (81.8%) patients were alive while 33 (18.2%) had died. Intravenous drug abuse, concurrent toxoplasma encephalitis and concurrent Pneumocystis jiroveci pneumonia independently predicted death outcome in both univariate and multivariate logistic regression analyses.